Lab-on-a-chip or Chip-in-a-lab: Challenges of Commercialization Lost in Translation. (2015) - Mohammed, Mazher Iqbal; Haswell, Steven; Gibson, Ian
Abstract: Lab-on-a-chip technology has been long envisaged to have tremendous commercial potential, owing to the ability of such devices to encapsulate a full range of laboratory processes in a single instrument and operate in a portable manner, rapidly and at low cost. Devices are believed to have potential in fields ranging across medical diagnostics, environmental sampling and a range of consumer products, however, to date very few devices have attained commercial success. This review examines the challenges relating to the commercialization of lab-on-a-chip technology from fundamental research to mass manufacturing and aims to provide insight to both academics and product development specialists the perceived hindrances to commercialization and a strategy by which future work could be translated into commercial success.